Fondaparinux or enoxaparin: A comparative study of postoperative bleeding in coronary artery bypass grafting surgery. - Landenhed Smith, Maya; Johansson, Malin; Erlinge, David ; 0000-0003-3042-5766; Olsson, Martin L ; 0000-0003-1647-9610; Bjursten, Henrik (Scandinavian cardiovascular journal : SCJ, 2010)
Objectives. Preoperative treatment with anti-coagulants for patients with non-ST-elevation acute coronary syndromes (NSTE-ACS) exposes patients undergoing surgical revascularization to a higher risk of perioperative bleeding. The aim of this study was to compare the effect on bleeding and transfusion needs during cardiac surgery for patients treated with enoxaparin or fondaparinux. Design. Using a combined retrospective and prospective approach, we studied the outcome of 147 patients with NSTE-ACS referred to coronary artery bypass grafting in terms of bleeding, blood transfusions and other complications. Results. Eighty patients were treated preoperatively with enoxaparin, and 67 patients with fondaparinux. There was no significant difference in postoperative bleeding (532 +/- 355 for enoxaparin group vs. 580 +/- 300 ml for fondaparinux group, p = ns) or transfusion needs for the two groups. A subgroup analysis of the fondaparinux group showed a significantly higher amount of postoperative bleeding after 12 h for patients when preoperative treatment with fondaparinux was discontinued less than 36 h prior to surgery compared to more than 36 h. Discussion. This study suggests that preoperative treatment with fondaparinux for NSTE-ACS is as safe as enoxaparin in terms of postoperative bleeding and transfusion needs. Findings support discontinuation of fondaparinux at 36 h prior to surgery.